Eggs Fertility, and Hatchability of Kampong Hens Inseminated Using Brahma, Cochin, and Bangkok Roosters Semen - Asnawi, Asnawi; Maskur, Maskur; Dradjat, Adji Santoso (Jurnal Biologi Tropis, 2025)
The objectives of this research were to evaluate Brahma, Cochin, Bangkok roosters spermatozoa quality and compare fertility and hatch-ability following insemination into Kampong hens. The semen quality was evaluated using a completely random design of three strains of the rooster with 5 replications. The results showed that spermatozoa concentrations of Brahma, Cochin, and Bangkok rooster were 1252.0± 7.92x106, 1140.0± 5.83x106, and 1304.0± 12.28x106 respectively (p >0.05). The percentage of motility of Brahma, Cochin, and Bangkok spermatozoa was 72 ± 2.74 %, 74 ± 2.24 %, and 73 ± 2.74 % respectively (p>0.05). The percentage viability of spermatozoa of Brahma, Cochin, and Bangkok were 99.2 ± 1.30 %, 99.4 ± 0.55 % dan 99.2 ± 1.10 % respectively (p>0.05). The percentage normality of Brahma, Cochin, and Bangkok spermatozoa were 94.6 ± 2.30 %, 94.4 ± 2.70 % dan 97.4 ± 2.07 % respectively (p >0.05). Fertility of eggs inseminated using Brahma, Cochin, and Bangkok, spermatozoa to Kampong hens were, 36.21 ± 17.52%, 34.29 ± 14.50%, and 73.27 ± 9.90% respectively and they were significantly different (p <0.05). The hatchability of eggs inseminated using Brahma, Cochin, and Bangkok spermatozoa were 59.40 ± 34.80%, 87.26 ± 8.81%, and 82.63 ± 5.34% respectively and they were significantly different (p<0.05). It can be concluded that Brahma, Cochin, and Bangkok roosters have good quality semen, which can be used inseminate into Kampong hens.